Investigation of the operating characteristics of a free-piston closed-cycle Joule engine generator with helium as working fluid - Benlei Wang; Shunmin Zhu; Ugochukwu Ngwaka; Boru Jia; Kumar Vijayalakshmi Shivaprasad; Yaodong Wang; Andrew Smallbone; Anthony Paul Roskilly; Ercang Luo (Energy Conversion and Management: X)
As an emerging micro- or small-scale energy conversion technology, linear Joule engine generators (LJEGs) combine the advantages of external combustion engines and linear generators, feature the advantages of high thermal-to-electrical efficiency, multi-fuel potential, good operational flexibility, a simple and compact mechanical structure, and low frictional loss. Earlier research on LJEGs mainly focused on open-cycle systems, while closed-cycle LJEGs, which are the subject of this work, have some unique characteristics in comparison with open-cycle ones. Unfortunately, the operating features of closed-cycle LJEGs are still not well comprehended. To fill this gap, in this paper, the operating characteristics of a closed-cycle LJEG with helium as working fluid are investigated based on a validated numerical model. The dynamic characteristics and output performance of the system were investigated at different system pressures and compared with an open-cycle LJEG with air as working fluid. The outcomes reveal that the closed-cycle LJEG has a smaller piston stroke and higher output efficiency. Furthermore, the effect of key parameters such as valve timing, electrical resistance coefficient, and cylinder diameters on system performance is investigated. This study offers in-depth insights into the operation characteristics of the closed-cycle LJEG, which contributes to the design of similar systems.